Gender gaps in time use and entrepreneurship - Pedro Bento; Lin Shao; Faisal Sohail (Bank of Canada, 2024)
The prevalence of entrepreneurs, particularly low-productivity non-employers, declines as economies develop. This decline is more pronounced for women. Relative to men, women are more likely to be entrepreneurs in poor economies but less likely in rich economies. We investigate whether gender gaps in time dedicated to non-market activities, which narrow with development, can account for this pattern. We develop a quantitative framework in which selection into occupations depends on one's ability and time and features gender-specific distortions and social norms around market work. When we calibrate the model to match cross-country data, we find that differences in social norms are almost entirely responsible for the patterns of gender gaps in both time use and entrepreneurship. Through affecting time use and entrepreneurship, social norms account for a substantial part of cross-country differences in output per worker and firm size and have significant welfare implications for women.
Keywords: J2; L2; O1; 330; Firm dynamics; Productivity